2013
DOI: 10.1017/s1368980013002279
|View full text |Cite
|
Sign up to set email alerts
|

Is the school food environment conducive to healthy eating in poorly resourced South African schools?

Abstract: Objective: To assess the school food environment in terms of breakfast consumption, school meals, learners' lunch box, school vending and classroom activities related to nutrition. Design: Cross-sectional survey. Setting: Ninety purposively selected poorly resourced schools in South Africa. Subjects: Questionnaires were completed by school principals (n 85), school feeding coordinators (n 77), food handlers (n 84), educators (n 687), randomly selected grade 5 to 7 learners (n 2547) and a convenience sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 26 publications
7
46
1
5
Order By: Relevance
“…Although some parents encouraged their children to make healthy purchases, for example, 37% of parents advised their children to purchase of fruit at school and 23% advised the purchase healthy foods, 24% of parents were not aware of the types of foods their children purchased at school. 44 The grade thus remained a C.…”
Section: School Tuck Shops Snacking Behaviors and Sugar-sweetenedmentioning
confidence: 97%
See 2 more Smart Citations
“…Although some parents encouraged their children to make healthy purchases, for example, 37% of parents advised their children to purchase of fruit at school and 23% advised the purchase healthy foods, 24% of parents were not aware of the types of foods their children purchased at school. 44 The grade thus remained a C.…”
Section: School Tuck Shops Snacking Behaviors and Sugar-sweetenedmentioning
confidence: 97%
“…Other smaller regional studies in younger age groups support this observation to varying degrees. 43,44,46 Many children were now receiving fruit and vegetables through the National Schools Nutrition Program (NSNP). 42 This was made possible by an increase in the average meal cost allowance per student per day since the last report card and the addition of a guideline to allow for fresh vegetables or fruit to be served daily.…”
Section: Nutritional Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…About one-third of the teachers in our study had not had any opportunities for in-service nutrition training. A South African study that considered the school food environment in relation to healthy eating revealed that most of the teachers showed interest in nutrition, but only 15% had received nutrition training (Faber et al 2013). It was further confirmed that providing training for teachers in all the learning areas of LO could facilitate healthy behavioral outcomes .…”
Section: Main Findingsmentioning
confidence: 96%
“…This finding is contrary to the U.S Department of Education survey on the teaching of nutrition, where one-third of the teachers taught nutrition as a separate subject, while the same proportion also taught nutrition by integrating it into other subjects (Celebuski and Farris 2000). In another South African study, 56% and 21% of educators taught nutrition as part of LO and NST, respectively (Faber et al 2013). …”
Section: Main Findingsmentioning
confidence: 99%